2012
DOI: 10.5811/westjem.2012.3.6899
|View full text |Cite
|
Sign up to set email alerts
|

Does Targeted Education of Emergency Physicians Improve Their Comfort Level in Treating Psychiatric Patients?

Abstract: Introduction:We determined if targeted education of emergency physicians (EPs) regarding the treatment of mental illness will improve their comfort level in treating psychiatric patients boarding in the emergency department (ED) awaiting admission.Methods:We performed a pilot study examining whether an educational intervention would change an EP’s comfort level in treating psychiatric boarder patients (PBPs). We identified a set of psychiatric emergencies that typically require admission or treatment beyond th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
0
5
0
1
Order By: Relevance
“…, Zun ) and that this lack of preparation can result in less‐than‐ideal MH patient management in ED (Marciano et al . ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…, Zun ) and that this lack of preparation can result in less‐than‐ideal MH patient management in ED (Marciano et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…An international study of ED physicians found that focused MH education improved their comfort in treating patients with an MI (Marciano et al . ). The variability in preparation, and acknowledged knowledge deficit, reveal a need for regular education and training to prepare emergency staff to care for patients with MI (Department of Human Services ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The resultant data may facilitate the linking of different risk levels of PEP with specific interventions or actions algorithms in EDs [ 41 ]. Thus, structured systems with clear algorithms for identifying and treating PEP could improve the comfort level of emergency room physicians in treating psychiatric patients [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The sources of funding were as follows: five federal (two NIH, one Canada, and one Taiwan), five universitysponsored, two industry-supported, and two organizationally funded. Research methodology included 17 surveys (36%), 17,19,21,25,30,31,33,37,40,42,46,[50][51][52]54,60,61 15 (31%) observational analyses, [14][15][16]22,23,27,32,33,38,44,47,49,56,57,59 and three (6%) qualitative methodology studies. 19,28,45 There were only 12 (25%) with an experimental or quasi-experimental study design, 20,24,26,35,36,39,41,43,48,53,55,57 with five of the highlighted articles using this rigorous design.…”
Section: Trends In Medical Education Research In 2012mentioning
confidence: 99%